2005
DOI: 10.1073/pnas.0506557102
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of hereditary coproporphyria

Abstract: Hereditary coproporphyria is an autosomal dominant disorder resulting from the half-normal activity of coproporphyrinogen oxidase (CPO), a mitochondrial enzyme catalyzing the antepenultimate step in heme biosynthesis. The mechanism by which CPO catalyzes oxidative decarboxylation, in an extraordinary metaland cofactor-independent manner, is poorly understood. Here, we report the crystal structure of human CPO at 1.58-Å resolution. The structure reveals a previously uncharacterized tertiary topology comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 68 publications
(65 reference statements)
2
66
0
Order By: Relevance
“…An aspartate interacting with a pyrrole NH group is proposed for E. coli PBGD and yeast and human CPOX (17,18,29). The central geometry of pyrrole's coordination by an aspartate, except in hUROD, is not identified in UPMT and CPOX, due mainly to the lack of the complex structures with a substrate or product.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An aspartate interacting with a pyrrole NH group is proposed for E. coli PBGD and yeast and human CPOX (17,18,29). The central geometry of pyrrole's coordination by an aspartate, except in hUROD, is not identified in UPMT and CPOX, due mainly to the lack of the complex structures with a substrate or product.…”
Section: Discussionmentioning
confidence: 99%
“…Anion coordination by the pyrrole nitrogen can create a cone conformation for the macrocycle (18). An aspartate interacting with a pyrrole NH group is proposed for E. coli PBGD and yeast and human CPOX (17,18,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficient activity of coproporphyrinogen III oxidase causes the accumulation and non-enzymatic oxidation of coproporphyrinogen, leading to neurological disturbances and skin photosensitivity 8 . The enzyme functions as a dimer in solution, and both the human 9 and yeast 10 enzymes have been crystallized and solved at good resolutions (2.0 Å for the yeast enzyme, and 1.58 Å for the human variant). Site-directed mutagenesis experiments have shown that several conserved residues (H131 11 , as well as R135, D274 and R275…”
Section: Introductionmentioning
confidence: 99%
“…The available crystal structures [9][10] show that coproporphyrinogen III oxidase may exist in two main conformations, distinguishable due to the relative position of helixes H2 (Ser79-Lys87) and H8…”
mentioning
confidence: 99%